Benthic marine litter accumulation at selection beaches in Ternate Island, Indonesia. Issue 1 (October 2020) - Lessy, M R; Najamuddin,
Abstract: The report of marine litter pollution first published in the scientific journal of the early 1970s; therefore, more than 40 years later, the scientist continues to understand the distribution of litter existing in the marine environment. The present study was carried out in Ternate Island, North Maluku Province (eastern Indonesia) which the aims are to determine litter composition, abundance, weight, and density on the seafloor and to predict the sources of seafloor litter distribution in the study areas. A conventional underwater visual survey with scuba/snorkeling. The depth of the sampling area varied between 3 and 6 m according to the slope of the island. During the survey, total of 1171 items were collected from all study sites and a total of 20.47 Kg of weight. The mass of overall debris concentration range from 0.089 items/m2 to 1.04 items/m2. The number percentage of plastic, metal, fibers/textiles, glass, and rubbers in total were 77%, 12%, 7%, 2%, and 2%, respectively. Plastic debris was the most dominant material category by means of number and weight.